The swinging flashlight test: flawed execution and interpretation in ophthalmological routine = Der Swinging-Flashlight-Test : mangelhafte Durchführung und Interpretation in der augenärztlichen Routine - Beisse, Flemming; Ring, Alina; Wilhelm, Helmut; Beisse, Christina (Klinische Monatsblätter für Augenheilkunde, 2020)
Background The swinging flashlight test is a standard diagnostic procedure to detect relative afferent pupillary defects. The advantages of the test lie within its objectivity and minimal effort. However, its value depends on its correct execution and interpretation. This questionnaire-based survey investigates whether this is given among German speaking ophthalmologists. Methods A multiple-choice questionnaire with 14 questions on the use of the swinging flashlight test was designed. It was presented to German speaking ophthalmology specialists (primary data) and orthoptists (secondary data) on specialist conferences or by telephone interviews. Results 249 ophthalmologists and 76 orthoptists participated in the survey. Only 2% of ophthalmologists answered all 14 questions correctly. On average 66% (range 29 - 100%) of the questions were answered correctly by the ophthalmologists. The question with the lowest result had a rate of 19%, the question with the highest result was correctly answered by 95%. The orthoptists achieved similar results. Conclusion The rate of correct answers appears disturbingly low. The swinging flashlight test being a basic tool and an obligatory test in a number of guidelines should rather be performed nearly error-free. In light of the high error rates, misdiagnoses and treatment errors must be feared. Better training seems necessary.